Mereformasi birokrasi publik Indonesia : studi perbandingan intervensi pejabat politik terhadap pejabat birokrasi di Indonesia dan Malaysia - azhari; Achidsti, Sayfa Auliya (Yogyakarta : Pustaka Pelajar, 2011)
Comparative studies on bureaucracy in Indonesia and Malaysia; cases of Sulawesi Tenggara, Indonesia and Sabah, Malaysia.
Revision of the author's thesis (doctoral)--Universitas Gadjah Mada, 2010.
'Peraturan perundang-undangan': p. 336-338.
Includes bibliographical references (p. 321-335) and index.
Keywords: Bureaucracy -- Indonesia -- Sulawesi Tenggara -- Case studies; Bureaucracy -- Malaysia -- Sabah -- Case studies; Executive-legislative relations -- Indonesia -- Sulawesi Tenggara -- Case studies; Executive-legislative relations -- Malaysia -- Sabah -- Case studies